<!--[if gte mso 9]> <![endif]--> Economic efficiency of Greek retail SMEs in a period of high fluctuations in economic activity: a DEA approach - D. Balios; N. Eriotis; A. Fragoudaki; D. Giokas (Applied Economics, 2015)
This study aims to analyse the economic efficiency of Greek small and medium retail enterprises before and after the crisis that started in 2008. Based on the Accounting Equation, we use Data Envelopment Analysis (DEA) to estimate variable returns of scale efficiency scores and to conclude on specific characteristics that efficient companies have, for example, on capital structure. Our results from the DEA application show a high degree of inefficiency. We found that SMEs on the islands are more efficient than those on the mainland and that SMEs in the cities are the least efficient. Size seems to be important, more so on the islands and on the mainland than in the cities. We conclude that companies should act more conservatively in terms of operating cost when the first signs of a recession appear. In addition, during a recession period, companies that have evidences that their operations will continue positively should strengthen their operations by raising more own capital. Finally, our study clarifies four issues: the efficiency of retail companies in a period of growth and a period of recession, focusing on SMEs that operate in different regions, connecting Accounting Equation and DEA and adding acid ratio as an output in our model.